EFEKTIVITAS LATIHAN KEKUATAN OTOT LENGAN TERHADAP KETEPATAN MEMANAH DI EKSTRAKURIKULER PANAHAN SISWA SMK NEGERI 3 LUBUKLINGGAU - Benny Marza Sugara; Sukasno Sukasno; Azizil Fikri ($$8@@&&$%K, 2022)
This study aims to determine student learning outcomes after the implementation of push up, dumbbell, and planks arm muscle strength exercises. The type of research used is quasi-experimental. The population of archery extracurricular students at SMK Negeri 3 Lubuklinggau is 20 students and the sample taken is 20 students. For sampling using the Census technique. Data collection using test techniques. The data collected after being analyzed using the z-test at a significant level = 0.05 obtained z_count = 8.73 z_table = 1.64 so that it can be concluded that the accuracy of archery at SMK Negeri 3 Lubuklinggau after the implementation of Arm Muscle Strength Training is significantly in the good category with an average value of students' archery accuracy results of 72.6.